1998
DOI: 10.1038/sj.jhh.1000596
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tumour necrosis factor and endothelin-1 between essential and renal hypertensive patients

Abstract: The present study was performed to compare circulating levels of tumour necrosis factor-␣ (TNF␣) and plasma endothelin 1 (ET-1), of hypertensive patients with or without renal failure and with those of normotensive healthy subjects. The study population consisted of 21 healthy normotensive subjects and 22 hypertensive patients, 11 with essential hypertension, and 11 with hypertension and chronic renal failure (CRF).Plasma ET-1 levels, serum TNF␣ and creatinine, creatinine clearance, 24-h urinary albumin excret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…5,6 Some reports 3,4,7 have shown a significant association between inflammatory markers and elevated BP, consistent with our findings. Kim et al 8 reported that TNF-a level correlated with the BP index and IL-6 level correlated with the BP variability index, implying that inflammation may be a mediator for the link between BP variability and target organ damage.…”
Section: Discussionsupporting
confidence: 82%
“…5,6 Some reports 3,4,7 have shown a significant association between inflammatory markers and elevated BP, consistent with our findings. Kim et al 8 reported that TNF-a level correlated with the BP index and IL-6 level correlated with the BP variability index, implying that inflammation may be a mediator for the link between BP variability and target organ damage.…”
Section: Discussionsupporting
confidence: 82%
“…(2) Hypertension is a major risk factor for cardiovascular disease and experimental evidence suggests that it may be an inflammatory stimulus which can promote expression of cytokines. (3)(4)(5)(6) A recent report has demonstrated a graded relationship between blood pressure and indices of inflammation, particularly interleukin-6, in apparently healthy men strengthening the postulated link between elevated blood pressure and inflammation. (7) The development of left ventricular hypertrophy (LVH) in hypertensive patients is an important negative prognostic sign associated with cardiovascular morbidity and mortality.…”
Section: Introductionmentioning
confidence: 95%
“…Cytokines appear to be important mediators of renal injury and the development of LVH. As noted, aging is associated with increased vascular stiffness and hypertension; and in particular, those with renal insufficiency have elevated levels of tumor necrosis factor [28]. In addition, studies have shown that elevated C-reactive protein levels in CKD patients were independent predictors of increased LV mass [29].…”
Section: Inflammationmentioning
confidence: 99%